IMPLEMENTASI SUPERVISI NON DIREKTIF DALAM MENINGKATKAN KOMPETENSI PROFESIONALISME GURU - Lutfiya, Amaliya Khoirun Nisa'; Binti Maunah; Mutohar, Prim Masrokan (Program Studi Manajemen Pendidikan Islam, 2024)
Teachers are expected to understand current professional standards and receive the necessary training to become more professional. Teachers may receive support or training to improve their professional skills through supervision. Organized training called supervision is intended to help teachers and other school personnel perform their duties well. The five main topics include (1) the definition of non-directive supervision; (2) the stages of implementing non-directive supervision; (3) the application of non-directive supervision; (4) efforts to improve the competence of teacher professionalism; (5) non-directive supervision in improving the competence of teacher professionalism. This research was written using library research methodology or literature study, which involves collecting information from books and journals on non-directive supervision strategies to improve teacher professionalism. The results showed that (1) indirect problem solving where the supervisor does not directly point out the problem, (2) the following non-directive stages; listening, providing reinforcement, explaining, presenting, and solving problems, (3) this non-directive supervision approach first listens to the problems faced by the teacher and then gives reinforcement related to the problem, (4) can be attempted by achieving the four teacher competencies as proclaimed by the regulations of the Minister of National Education, (5) the role of the principal is considered very important where teachers become professional there are various approaches, one of which is a non-directive approach.